The Psycholinguistic Characteristics of Grammar Manipulatives - Hordienko-Mytrofanova, Iya; Kaznacheyeva, Yana (East European Journal of Psycholinguistics, 2014)
The article focuses on the description of manipulative games as a means of emotional memory enhancement. Manipulative games basically consist of structural and functional models, i.e. “MASP” grammar manipulatives, where MASP stands for “model, algorithm, and speech pattern”. The combination “speech pattern – model – algorithm” is utterly explicit and corresponds to completely controlled and object-oriented activity (Piotr Galperin). A manipulative is a complex type of learning input, since a manipulative model contains both an explicit algorithm of fulfilling grammar operations and a speech pattern. The “MASP” grammar manipulatives are designed to develop English grammar skills up to the stage of automaticity. The present paper deals with the manipulative games called “MASP-Tenses”. They help students learn verb tenses and give a solid understanding of sentence structure. The manipulative games are largely based on Galperin’s theoretical framework (theory of a step-by-step formation of mental action), as well as the principle of visualization in terms of action materialization. According to Galperin’s theory the successful development of grammar skills depends on the completeness and pattern of object-oriented activity. To perform grammar operations it is crucially important to create an object-oriented basis of an activity in terms of revealing structural relations within a verbal text. It is the structural relations that most adequately express the linguistic specificityof the target language. The negative affective characteristics of students, in particular anxiety and lack of confidence, are associated with the lack of orientation. Second language acquisition requires students’ attention and their volition. Thus, manipualtives are the most “emotionally favourable” form of presenting structural relations of linguistic phenomena, as they provide completely controlled and object-oriented basis of students’ activity while performing grammar operations. However, the only way to significantly reduce students’ anxiety and consequently increase their self-confidence is to use additional didactic material which reflects the functioning of grammar material in speech activity and helps to reduce the orientation-related part of a grammar operation. References • Ann, S. (2011). As I was saying: how and why to teach discourse markers. The Busy Teacher Library. Retrieved from http://www.busyteacher.org/10076-how-and-why-to-teachdiscourse-markers.html • Camiciottoli, B. C. (2003). Metadiscourse and ESP reading comprehension: An exploratory study. Reading in a Foreign Language, 15(1), 28–44. • Cheng, X., & Steffensen, M. S. (1996). Metadiscourse: A technique for improving student writing. Research in the Teaching of English, 149–181. • Crismore, A. ( 1989). Talking with Readers: Metadiscourse as Rhetorical Act. New York, NY: Peter Lang. • Crismore, A., & Abdollehzadeh, E. (2010). A review of recent metadiscourse studies: The Iranian context. Nordic Journal of English Studies, 9(2), 195–219. • Crismore, A., Markkanen, R., & Steffensen, M.S. (1993). Metadiscourse in persuasive writing. Written Communication, 10(1), 39–71. doi: 10.1177/0741088393010001002. • Dastjerdi, H. V., & Shirzad, M. (2010). The Impact of explicit instruction of metadiscourse markers on EFL learners’ writing performance. The Journal of Teaching Language Skills (JTLS),2(2).154–175. • Davaei, R., & Karbalaei, A. (2013). Interpersonal Metadiscourse in Compositions Written by Iranian ESP Students. European Online Journal of Natural and Social Sciences, 2(2s), pp-291. • Dhieb-Henia, N. (2003). Evaluating the effectiveness of metacognitive strategy training for reading research articles in an ESP context. English for Specific Purposes, 22(4), 387–417. • Erfani, S. M., Iranmehr, A., & Davari, H. (2011). Deepening ESP reading comprehension through visualization. Journal of Language Teaching and Research, 2(1), 270– 273. • Halliday, M.A.K. & Hasan, R. (1976). Cohesion in English. London: Longman group Ltd. • Hudson, T. (1991). A content comprehension approach to reading English for science and technology. Tesol quarterly, 25(1), 77–104. • Hyland, K. (2000). Disciplinary discourse: Social interactions in academic writing. London: Longman. • Hyland, K. (2001). Bringing in the reader: Addressee features in academic articles. Written Communication, 18(4), 549–574. • Hyland, K. (2004). Disciplinary Interactions: Metadiscourse in L2 Postgraduate Writing. Journal of Second Language Writing, 13,133–151. • Hyland, K. (2005). Metadiscourse: Exploring interaction in writing. London: Bloomsbury Publishing. • Parvaresh, V. & Nemati, M. (2008). Metadiscourse and Reading Comprehension: The Effects of Language and Proficiency. Electronic Journal of Foreign Language, 5(2), 220–239. • Tajeddin, Z. & Alemi, M. (2012). L2 Learners’ Use of Metadiscourse Markers in Online Discussion Forums. Issues in Language Teaching, 1(1), 93–121. • Vande Kopple, W. J. (2002). Metadiscourse, discourse, and issues in composition and rhetoric. In F.Barton & C.Stygall (Eds.), Discourse Studies in Composition (pp. 91–113). Cresskill, NJ: Hampton Press. • Williams, J. M. (1981). Ten Lessons in Clarity and Grace. University of Chicago Press, Chicago.